إدارة الأزمات في ضوء العقيدة: غزوة تبوك نموذجاً - Soma`ah, `Abduh `Abdullah; Buang, Ahmad Hidayat (Afkar: Jurnal Akidah dan Pemikiran Islam, 2013)
A unique aspect of the genius of prophet Muhammad (PBUH) in management science in the light of the Islamic faith was revealed through the way he behaved in crisis management during that era. The author applied one model; the battle of Tabuk, which is considered one of the greatest crisis that prophet Muhammad (PBUH) and his companions have faced. They overcame this crisis successfully and turned it into a big victory. The author studied and analysed this crisis using some modern methods of the management science in the light of faith.